Search for a possible isotope effect in charge-changing collisions involving hydrogen and deuterium - Salvatelli, E. R.; Lantschner, G.; Meckbach, W. (1969)
Fil: Salvatelli, E. R. Comisión Nacional de Energía Atómica; Argentina